Resilience requirements. Adaptive methodology for the housing emergency - Ilaria Montella (Agathón, 2019)
The exposure to many risk factors related to climate change, scarcity of resources, migration and a critical economic situation place cities under constant stress and instability. Therefore, increasing their resilience is required. Arup developed the City Resilience Framework for the 100 Resilient Cities project. This framework places housing among the action sectors to enhance resilience. This analysis borrows best practices for resiliency from case study analyses while investigating how architecture can contribute to the Framework. It then proposes a meta-design tool in the form of Design Technical Data Sheets. These are meant to support the actors involved in design processes with resilience-oriented design and procedural guidelines.